ANALYSIS OF THE EFFECTIVENESS OF THE PERSONNEL INFORMATION SYSTEM IN SUPPORTING HUMAN RESOURCES DATA MANAGEMENT ADMINISTRATION AT MANADO STATE UNIVERSITY - Stenli Ferlan Rattu; Margareth Inof Riisyie Rantung; Jeane Mantiri (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aims to analyze the effectiveness of the Personnel Information System in supporting human resources (HR) data management administration at Manado State University (UNIMA). This research employs a qualitative approach using a case study design. Data were collected through three main methods: in-depth interviews, participant observation, and document review. The findings reveal that the effectiveness of the personnel information system at UNIMA remains very low. This is primarily due to the absence of a comprehensively integrated system, resulting in HR data management heavily relying on manual methods and simple software like Microsoft Excel. Although the university has made digital transformation efforts, such as developing the Key Performance Indicators (MPI) management information system and collaborating with Ganesha University of Education (Undiksha) for system adoption, these initiatives remain partial and have not encompassed the entire personnel management cycle. Consequently, the system's ineffectiveness causes systemic impacts, including administrative delays in employee promotions and reporting, errors in staff planning, and potential threats to study program accreditation. Furthermore, it causes the institution to fail in implementing the principles of Good University Governance (GUG) and the legally mandated merit system. Therefore, improving the personnel system at UNIMA requires strategic steps, including issuing formal policies, continuously enhancing HR capacity and infrastructure, and developing an integrated system specifically tailored to the university's needs.